An Introvert's Guide to Academic Leadership - Jeff Buller (Academic Chairpersons Conference Proceedings, 2018)
Higher education contains a high percentage of people who are more introverted than extroverted. They find social gatherings and other large meetings to be emotionally draining. Many academic leaders actually hate making phone calls, prefer to eat meals alone, and need a great deal of “alone time” in order to recharge. This workshop explores two strategies that introverts can use for increasing their effectiveness as academic leaders: taking advantage of their strengths and compensating for their challenges. It also considers ways in which introverts may sometimes be even more effective leaders than extroverts.
Keywords: Introvert Leadership Academic Administration Extrovert